Bidirectional triplet exciton transfer between silicon nanocrystals and perylene. Issue 19 (20th April 2021) - Huang, Tingting; Koh, Timothy T.; Schwan, Joseph; Tran, Tiffany T.-T.; Xia, Pan; Wang, Kefu; Mangolini, Lorenzo; Tang, Ming L.; Roberts, Sean T.
Abstract : We demonstrate that silicon quantum dots can exchange spin triplet excitons with molecules covalently attached to their surface. Such hybrid materials can enable systems that upconvert incoherent far-red light into the visible spectral range. Abstract : Hybrid materials comprised of inorganic quantum dots functionalized with small-molecule organic chromophores have emerged as promising materials for reshaping light's energy content. Quantum dots in these structures can serve as light harvesting antennas that absorb photons and pass their energy to molecules bound to their surface in the form of spin-triplet excitons. Energy passed in this manner can fuel upconversion schemes that use triplet fusion to convert infrared light into visible emission. Likewise, triplet excitons passed in the opposite direction, from molecules to quantum dots, can enable solar cells that use singlet fission to circumvent the Shockley–Queisser limit. Silicon QDs represent a key target for these hybrid materials due to silicon's biocompatibility and preeminence within the solar energy market. However, while triplet transfer from silicon QDs to molecules has been observed, no reports to date have shown evidence of energy moving in the reverse direction. Here, we address this gap by creating silicon QDs functionalized with perylene chromophores that exhibit bidirectional triplet exciton transfer. Using transient absorption, we find triplet transfer from silicon to perylene takes place over 4.2 μs while energy transfer in the reverse direction occurs two orders of magnitude faster, on a 22 ns timescale. To demonstrate this system's utility, we use it to create a photon upconversion system that generates blue emission at 475 nm using photons with wavelengths as long as 730 nm. Our work shows formation of covalent linkages between silicon and organic molecules can provide sufficient electronic coupling to allow efficient bidirectional triplet exchange, enabling new technologies for photon conversion.